2017
DOI: 10.1063/1.4978666
|View full text |Cite
|
Sign up to set email alerts
|

Realization of direct bonding of single crystal diamond and Si substrates

Abstract: Diamond/Si junctions have been achieved by surface activated bonding method without any chemical and heating treatments. Bonded interfaces were obtained that were free from voids and mechanical cracks. Observations by using transmission electron microscopy indicated that an amorphous layer with a thickness of ∼20 nm across the bonded interface was formed, and no structural defects were observed at the interface. The amorphous layer of the diamond side was confirmed to be the mixture of sp2 and sp3 carbons by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…For the room temperature direct bonding, the surface roughness of bonding materials is a very important factor. The R a value of bonding material surface smaller than 1 nm was necessary for achieving the direct bonding of diamond and semiconductor substrates [11,13]. Although the R a value (2.93 nm) of the InGaP surface was larger than 1 nm, the direct bonding of diamond and InGaP was achieved.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For the room temperature direct bonding, the surface roughness of bonding materials is a very important factor. The R a value of bonding material surface smaller than 1 nm was necessary for achieving the direct bonding of diamond and semiconductor substrates [11,13]. Although the R a value (2.93 nm) of the InGaP surface was larger than 1 nm, the direct bonding of diamond and InGaP was achieved.…”
Section: Resultsmentioning
confidence: 97%
“…The room temperature bonding of diamond and GaN using a silicon amorphous layer by SAB method has been demonstrated [9,10]. In addition, the room temperature direct bonding of diamond and Si using the SAB method has also been reported [11,12]. In SAB, the substrate surfaces are activated by Ar fast-atom beam irradiation under ultra-high vacuum conditions, and then the activated surfaces are contacted together by applying pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A large numbers of small size diamonds bonded to a large diameter Si substrate could be used as a large diameter diamond substrate. We previously reported that the direct bonding of diamond and Si by surface activated bonding (SAB) at room temperature [19]. We demonstrated diamond/Si bonding interface with a full contact area of 4 × 4 mm 2 and good thermal stability at temperature of 1000 °C for 12 h [20].…”
Section: Introductionmentioning
confidence: 90%
“…SAB was used for fabricating a variety of heterostructures such as GaAs/Si, 5) 4H-SiC/Si, 6) GaAs/SiC, 7) and GaAs/GaN, 8) heterostructures. The direct bonding of single-crystal diamond and Si by SAB was demonstrated by J. Liang et al 9) In the previous paper, diamond/Si bonding interface with full contact area and high thermal stability were not achieved. Although the heating of the bonding samples is not required during SAB process, a high temperature of about 1000 °C lasting long time is necessary for the diamond epitaxial growth.…”
mentioning
confidence: 98%